Analysis and definition of data flows generated by bio stimuli in the design of interactive immersive environments - Gomes, Paulo Sérgio Machado Veloso (2021)
This work focuses on interactivity as one of the essential factors for creating immersive environments, particularly interactivity that generates involuntary responses over which the user does not have conscious control. A dynamic and adaptive model was designed to analyze and define the data flow generated by bio stimuli for the design of interactive immersive environments.